Pengukuran Tingkat Kematangan Sistem Informasi Akademik STIE XYZ Menggunakan Framework COBIT 5 Domain MEA01 - Ibrahim Fuad (Universitas Mercu Buana Yogyakarta, 2024)
STIE XYZ is a private high school located in Pasuruan Regency, East Java. In management related to student academics, STIE XYZ has used an academic information system to facilitate the Academic and Student Administration in managing student data such as grades, KRS, KHS, and other important data. In running an information system, it is necessary to measure the maturity level to find out whether the information system is running as desired. However, the academic information system at STIE XYZ has not yet measured its maturity level technically and structured. In this study, the measurement of the maturity level of the STIE XYZ academic information system focused on the process of monitoring, evaluating and evaluating performance, and the suitability of information technology performance, using the MEA01 (Monitor, Evaluate and Assess Performance, and Comformance) domain in the COBIT 5 framework. aims to determine the maturity level of the Process Capability Model (PCM) of the application of academic information systems at STIE XYZ. With this research, it is hoped that the institution will be able to determine the suitability between the current conditions and the desired conditions in the STIE XYZ academic information system.